Pemikiran Politik Islam Imam Al-Mawardi dan Relevansinya di Indonesia - Muhajir, Muhajir (Prodi Tata Negara (Siyasah) IAIN Langsa, 2023)
Al-Mawardi's thoughts are still being studied, especially by academics who focus on the study of Islamic politics. Many different political concepts are offered by Islamic thinkers. But that concept offered by al-Mawardi is very interesting to discuss, especially in the context of the State of Indonesia. This paper aims to look at the characteristics of Imam al-Mawardi's political thought and its relevance in the context of the present, especially politics in Indonesia. This paper was produced from a literature study by examining a book written directly by al-Mawardi entitled Al-Ahkam as-Sulthaniyyah. The historical and ethnographic approaches in this paper seek to examine and analyze the political patterns initiated by Imam Al-Mawardi. Resultsstudy This shows that there are six political elements that must be met by every leader, namely: first, religion that is embraced and lived as a moral force; second, a charismatic ruler; third, comprehensive justice; fourth, even security; fifth, sustained soil fertility; sixth, hope of survival. In the Indonesian context, leaders should have six characters offered by Imam Al-Mawardi to run the government.